O corpo e outras paisagens: fragmentos de uma clínica em construção - Zamborlini, Lucelia dos Santos (2014)
The body and other landscapes: fragments from a clinical practice in process is a cartography of clinical work from the perspective of body psychotherapy. Using fragments taken from my clinical notes, I investigate and elaborate upon questions regarding proposed interventions, analyzing their effects, not only with the patients but also with the therapist who is building a clinical practice